Evaluation of stakeholder opinion about Long Term Care Facilities for People with Dementia perceived quality: a web-based survey in the Italian context - Mangili, Silvia; Ciaffoni, Luca; Sun, Tianzhi; Brambilla, Andrea; Capolongo, Stefano (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Italy is a country where the percentage of elderly population is very high (23% over 65). The aim of the investigation is to bring out which aspects of the spaces intended to accommodate elderly People with Dementia pathologies should be most present and potentially interested in becoming cornerstones of a new model of Long-Term Care facilities (LTC).Methods: This research uses a case studies analysis followed by a web based survey as methodological tools. The questions were identified following an analysis of recent European case studies. The survey has been submitted to a panel of stakeholders (users, pratictioner, designer and manager in the healthcare sector). It is articulated in eight items touching on functional, configurational, and perceptual aspects of the LTC.Results: The 210 responses received provided a basis for comparison with the trend lines detected by the case study analysis, establishing continuity on some configurational aspects and providing divergent views for others. The research found a strong need to introduce new service activities and technologies aimed at the care and assistance of guests with dementia. These specific needs often involve the introduction of new spaces and environments or the redefinition of the same, where already present.Conclusions: The results highlights that a new model of residence must incorporate new technological applications, outdoor spaces, that are perceived significantly by both patients and practitioners, and improve well-being of all users.